1999
DOI: 10.1302/0301-620x.81b3.9234
|View full text |Cite
|
Sign up to set email alerts
|

Endoprosthetic replacement of the proximal tibia

Abstract: We have performed endoprosthetic replacement after resection of tumours of the proximal tibia on 151 patients over a period of 20 years. During this period limb-salvage surgery was achieved in 88% of patients with tumours of the proximal tibia. Both the implant and the operative technique have been gradually modified in order to reduce complications. An initial rate of infection of 36% has been reduced to 12% by the use of a flap of the medial gastrocnemius, to which the divided patellar tendon is attached. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(71 citation statements)
references
References 0 publications
5
66
0
Order By: Relevance
“…Biau et al [4] studied 26 patients with allograft-prosthetic components and found a mean extensor lag of 7.7°. However, comparing our results with those from other series [5,22,38] using medial gastrocnemius flap reconstructions, we observed a slightly better outcome in our patients. Bickels et al [5], for example, reviewed 55 patients during a 20-year period and found full extension to an extension lag of 20°in 44 (78%) patients, an extensor lag of 20°to 30°in 10 (19%) patients, and one greater than 40°in one (3%) patient.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Biau et al [4] studied 26 patients with allograft-prosthetic components and found a mean extensor lag of 7.7°. However, comparing our results with those from other series [5,22,38] using medial gastrocnemius flap reconstructions, we observed a slightly better outcome in our patients. Bickels et al [5], for example, reviewed 55 patients during a 20-year period and found full extension to an extension lag of 20°in 44 (78%) patients, an extensor lag of 20°to 30°in 10 (19%) patients, and one greater than 40°in one (3%) patient.…”
Section: Discussionsupporting
confidence: 70%
“…Unfortunately, full extension was not defined by a lag of 0°, which does not allow further comparison with other reports. The mean extensor lag of 50 patients studied by Grimer et al [22] was 30°. When using a medial gastrocnemius flap, there is debate regarding whether to augment the attachment with some kind of synthetic material [3,5,7,9,14,20,24,31,[37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Kendall et al [16] reported functional deficits were mainly the result of a compromised extensor mechanism. Avulsion of the patellar ligament is one mechanism of compromising the extensor mechanism, with a reported incidence of 10.5% to 100% [1,13]. In the absence of patellar ligament avulsion, attenuation may occur without complete avulsion.…”
Section: Introductionmentioning
confidence: 99%